ANALISA UJI KINERJA MESIN PENGAYAK PASIR MENGGUNAKAN PIRINGAN AYAK DENGAN METODE GERAK EKSENTRIK KAPASITAS 1 M3/JAM - Irfandi, Irfandi; Sutrisno, Franky; jufrizal, Jufrizal; Eswanto, Eswanto (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2017)
Sand is a material that is very much needed for building materials. This sand material may still be mixed with stones or gravel. To get this fine sand material, the process of pengayaka is carried out. Characteristics of sand are dry sand, half wet sand, wet sand. In terms of HR, this perpetuation process still requires relatively large time and costs. Sand sieving machine using a sieve disk device with eccentric motion method after the speed is made must still be solved, for example the machine has answered the problem above. Because good results will certainly increase the value of work as well as vice versa. This measurement is done to determine the production capacity, power at the time of sifting sand, and sand density. From the test results obtained on the type of dry sand density of 1.414 kg/liter total capacity of 3.132 m3/hr, type of half sand wet density 1,551 kg / liter total capacity 1,461 m3 / hour, type of wet density 1,651 kg /liter total capacity 0,791 m3/hour. From the results of electromotor testing, it was obtained a power of 170 Watt. No-load testing obtained power of 452.83 Watt, capable of providing 454.59 Watt of power for testing with dry sand loads. Where as for testing with half-wet sand load produces 458.01 Watt of power, and to calculate with wet sand load the power is 463.32 Watt. At the time of this sand sieving the results of its capacity are very beneficial in the type of sand, and in the presence of tribal density. From the results of the test data that is done does not affect the capacity and density is more open to capacity.